Youth Solar Ultraviolet Radiation Exposure, Concurrent Activities and Sun-protective Practices: A Review - Wright, C. Y.; Reeder, A. I. (Photochemistry and photobiology, 2005)
To assist standardization of procedures, facilitate comparisons, and help guide research efforts to optimally inform development of appropriately targeted interventions, there is a need to review methods used to quantify child and adolescent solar ultraviolet radiation (UV) exposure, related outdoor activities and sun-protective practices. This holistic approach is essential for comprehensive research that will provide all-inclusive, informative and meaningful messages for preventive measures of harmful UV exposure. Two databases were searched and 29 studies were retrieved, and these studies report measurement or assessment techniques documenting UV exposure patterns and related outdoor activities. Polysulfone film badges were the main measurement instrument used in 10 studies, with questionnaire, survey data, observation, a model, electronic dosimeters, biological dosimeters, colorimeter and UV colouring labels used in the remaining studies. Methods used to record activities included self-report, parental report, a logbook and observation. Measurement duration and unit of UV exposure varied in most studies, but a method common to 15 studies was measured UV exposure as a percentage of ambient UV. The studies reviewed do not provide sufficient information for the development and evaluation of targeted youth sun protection programs. Studies are required which document precise UV exposure, concurrent activities and sun protection usage for children and adolescents.